Nature of the spin-glass phase in dense packings of Ising dipoles with random anisotropy axes. (1st August 2017) - Alonso, Juan J; Allés, B
Abstract: Using tempered Monte Carlo simulations, we study the the spin-glass phase of dense packings of Ising dipoles pointing along random axes. We consider systems of dipoles (i) placed on the sites of a simple cubic lattice with lattice constant d, and (ii) placed at the center of random close packed spheres of diameter d that occupy 64% of the volume. For both cases, we find a spin-glass phase below a certain temperature T sg . By analysing the data obtained for the overlap parameter, the associated correlation length, as well as the statistics of the overlap distributions of individual samples, we find a behavior consistent with quasi-long-range order in the spin-glass phase, similar to the one previously found in strongly diluted dipolar systems.